(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The Linguistic Significance of Blessings and Farewell Rituals One of the most emotional moments in the wedding process is when the bride bids farewell to her family. This departure is accompanied by sorrowful songs and poetic blessings, emphasizing the deep emotional ties between the bride and her parents.